Changes in thyroid status of Menidia beryllina exposed to the antifouling booster irgarol: Impacts of temperature and salinity - Moreira, Lucas Buruaem [UNESP]; Diamante, Graciel; Giroux, Marissa; Xu, Elvis Genbo; Souza Abessa, Denis Moledo de [UNESP]; Schlenk, Daniel (Elsevier B.V., 2018)
The triazine-based herbicide irgarol is widely used in antifouling systems as an algicide and has been detected recently in multiple coastal environments. Studies evaluating sub-lethal responses of fish following exposure to irgarol are limited. Moreover, impacts of climate change on fish endocrinology may also contribute to the sublethal toxicity of irgarol. We assessed the effects of irgarol on thyroid endpoints in juveniles of Menidia beryllina under two different treatments of salinity (10 and 20 parts per thousand) and two temperatures (10 and 20 degrees C). Condition factor coefficients (K) of animals were significantly affected by 0.1 to 10 mu g/L of irgarol at the higher temperature. Levels of T3 were changed in whole body homogenates from both temperatures at 10%0 following exposure to 1 to 10 mu g/L T4 levels were altered only at 10 degrees C when animals were treated with 1 to 10 mu g/L (10 parts per thousand), and in 0.1 and 10 mu g/L (20 parts per thousand). Increased transcripts of deiodinase enzymes at 10 degrees C may be impacted by salinity and alter thyroid hormone homeostasis. Impact on gene expression of thyroid (alpha and beta) and growth hormone receptors were also determined. Our results highlight the relevance of environmental variable that may impact the ecological risk of irgarol in estuarine systems. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Biocides; Climate change; Estuary; Endocrine disrupting chemicals; Fish endocrinology; Inland silversides